2018
DOI: 10.1097/jom.0000000000001364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genetic Polymorphism on Susceptibility to Nephrotoxic Properties of BTEXs Compounds

Abstract: These findings indicate that individuals carrying null GSTT1 or null GSTT1/GSTM1 are more susceptible to nephrotoxic properties of BTEXs compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…38 Nevertheless, it has been shown that individuals may respond differently to these toxins under similar exposure conditions, and early clues suggest the role of individual genetic differences. 25,27,34 Our analysis showed that the T allele of ATM -rs228589 A>T was significantly more prevalent in cases than the control individuals. In AA) with a high risk of abnormal hematological indices.…”
Section: Ta B L E 3 Data On Hematological Indicesmentioning
confidence: 69%
See 4 more Smart Citations
“…38 Nevertheless, it has been shown that individuals may respond differently to these toxins under similar exposure conditions, and early clues suggest the role of individual genetic differences. 25,27,34 Our analysis showed that the T allele of ATM -rs228589 A>T was significantly more prevalent in cases than the control individuals. In AA) with a high risk of abnormal hematological indices.…”
Section: Ta B L E 3 Data On Hematological Indicesmentioning
confidence: 69%
“…It is now clear that the level of susceptibility of individuals to the effects of toxicants such as BTEXs is variable, often due to genetic differences 27,30,31,34,35 . Revealing such a genetic predisposition can be very important for exposure risk assessment and early detection and prevention of related diseases in susceptible individuals 1,30,31,36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations